2015
DOI: 10.1155/2015/534952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Luteolin and Apigenin on the Expression of Oct-4, Sox2, and c-Myc in Dental Pulp Cells withIn VitroCulture

Abstract: Introduction. Dental pulp cells (DPCs) are promising cell source for dental tissue regeneration. Recently, small molecules which optimize microenvironment or activate the reprogramming network provide a new way to enhance the pluripotency. Two promising bioflavonoids luteolin and apigenin were reported to enhance reprogramming efficiency in mouse embryonic fibroblast (MEF). However, their effect and underlying mechanism in cell fate determination of human DPCs remain unclear. Methods. To elucidate the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…In this context as VRK1 reaches a high level, it is able to activate CCND1 by itself and also down-regulate SOX2 by an unknown mechanism but that is likely to include regulation of the transcriptional complex. This latter effect is consistent with the upregulation of pluripotency transcription factors, Sox2, Oct4 and c-myc, caused by luteolin, an inhibitor of VRK1 50 . Moreover, high VRK1 can stabilize p53 19 51 and contribute to the necessary cell cycle arrest to permit differentiation.…”
Section: Discussionsupporting
confidence: 81%
“…In this context as VRK1 reaches a high level, it is able to activate CCND1 by itself and also down-regulate SOX2 by an unknown mechanism but that is likely to include regulation of the transcriptional complex. This latter effect is consistent with the upregulation of pluripotency transcription factors, Sox2, Oct4 and c-myc, caused by luteolin, an inhibitor of VRK1 50 . Moreover, high VRK1 can stabilize p53 19 51 and contribute to the necessary cell cycle arrest to permit differentiation.…”
Section: Discussionsupporting
confidence: 81%
“…Contextualizing, it is likely that when VRK1 accumulates, it is able to activate CCND1 by itself and also downregulate SOX2 by an unknown mechanism. This latter outcome is consistent with the upregulation of pluripotency transcription factors, Sox2, Oct4 and c-myc, observed upon luteolin treatment, an inhibitor of VRK1 (Kim et al, 2014;Liu et al, 2015). Moreover, high expression of VRK1 can stabilize p53 and consequently contribute to the necessary cell cycle arrest to permit differentiation.…”
Section: Implication Of Vrk1 and Sox2 On The Regulation Of Cell Prolisupporting
confidence: 80%
“…Oct4 and Sox2 levels in human embryonic stem cells (hESCs) characterize the undifferentiated state, and loss expression of Oct4 and Sox2 resulted in cell differentiation and progressive loss of pluripotency . Recent studies have reported that hDPCs can be rejuvenated by optimizing the extracellular microenvironment, which regulates pluripotency‐related genes such as Stro1, Oct4, and Sox2 to modulate cells' regenerative properties …”
Section: Discussionmentioning
confidence: 99%
“…28 Recent studies have reported that hDPCs can be rejuvenated by optimizing the extracellular microenvironment, which regulates pluripotency-related genes such as Stro1, Oct4, and Sox2 to modulate cells' regenerative properties. 22,29 Applying growth factors to a culture solution is a simple and effective way to improve the microenvironment for stem cells. 30 In particular, bFGF has been reported to enhance cell proliferation and pluripotency through the Smad, PI3K/Akt, and Wnt1/b-catenin signaling pathways in hESCs.…”
Section: Discussionmentioning
confidence: 99%